Decoupling the effects of confinement and passivation on semiconductor quantum dots. Issue 29 (7th July 2016) - Rudd, Roya; Hall, Colin; Murphy, Peter J.; Reece, Peter J.; Charrault, Eric; Evans, Drew
Abstract : Plasma synthesised Si QDs are deposited in liquids to decouple confinement and passivation effects on their optical properties. Abstract : Semiconductor (SC) quantum dots (QDs) have recently been fabricated by both chemical and plasma techniques for specific absorption and emission of light. Their optical properties are governed by the size of the QD and the chemistry of any passivation at their surface. Here, we decouple the effects of confinement and passivation by utilising DC magnetron sputtering to fabricate SC QDs in a perfluorinated polyether oil. Very high band gaps are observed for fluorinated QDs with increasing levels of quantum confinement (from 4.2 to 4.6 eV for Si, and 2.5 to 3 eV for Ge), with a shift down to 3.4 eV for Si when oxygen is introduced to the passivation layer. In contrast, the fluorinated Si QDs display a constant UV photoluminescence (3.8 eV) irrespective of size. This ability to tune the size and passivation independently opens a new opportunity to extending the use of simple semiconductor QDs.